ANALISIS KETAHANAN HIDUP PENDERITA TUBERKULOSIS DENGAN MENGGUNAKAN METODE REGRESI COX KEGAGALAN PROPORSIONAL (Studi Kasus di Puskesmas Kecamatan Kembangan Jakarta Barat) - Wulan Safitri; Triastuti Wuryandari; Suparti Suparti (Jurnal Gaussian, 2016)
Tuberculosis (TB) is an infectious disease caused by the bacteria of the Mycobacterium groups that is Mycobacterium Tuberculosis. Most of the TB germs attack the lungs, but can also on other organs. In Indonesia based on the Survei Kesehatan Rumah Tangga (SKRT) in 2001 showed TB is the first cause of death in the group of infectious diseases. To determine the factors that affect the rate of healing of patients with TB is using regression analysis, because the dependent variable is the time of failure that equipped with censorship then used cox proportional hazard regression. Cox proportional hazard regression is a regression model that is often used in survival analysis. Survival analysis is the phrase used to describe the analysis of data in the form of times from a well-defined time origin until the occurrence of some particular event or end-point. The cases examined in this study are the factors that affect the rate of healing of patients with TB in Puskesmas Kecamatan Kembangan Jakarta Barat. The conclusion state that the factors affecting the rate of healing of patients with TB are a source of transmitting and medicine records. Keywords: Tuberculosis, Survival Analysis, Cox Proportional Hazard Regression